2013
DOI: 10.5296/ast.v1i2.3558
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Chemical Compound and Antibacterial Activity Test of Kopasanda (Chromolaena Odorata L.) Leaf Extract Against Vibriosis-Causing Vibrio harveyi (MR 275 Rif) on Tiger Shrimp

Abstract: Kopasanda (Chromolaena odorata L.) R.M King and H. Rob were classified as blossoming bush species in the Asteraceae family. An empirical study showed that kopasanda (C. odorata L.) leaf had been used by the embankment farmers at South Sulawesi Province to eradicate Vibriosis which caused death for tiger prawn (P.monodon Fabr.). The objective of research was to understand the bioactive compound that was contained within kopasanda (C. odorata L.) leaf extract and its antibacterial activity against V. harveyi. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
6
1
2
Order By: Relevance
“…Thus, fraction 3 of Majapahit fruit (inhibition zone of 23.11 mm) had a strong inhibitory response against bacterial growth. Compared with the previous studies with the same bacteria V. harveyi, the inhibition zones observed in this study were lower than those observed in the study by Harlina et al [8] who reported an inhibition zone of ~19 mm produced by Kopasanda (C. odorata L.) leaf extract. The measurements are higher than those reported for pomegranates (26 mm), apples (20 mm), and lemons (20 mm) against Staphylococcus aureus [13].…”
Section: Antibacterial Activity Testcontrasting
confidence: 94%
See 2 more Smart Citations
“…Thus, fraction 3 of Majapahit fruit (inhibition zone of 23.11 mm) had a strong inhibitory response against bacterial growth. Compared with the previous studies with the same bacteria V. harveyi, the inhibition zones observed in this study were lower than those observed in the study by Harlina et al [8] who reported an inhibition zone of ~19 mm produced by Kopasanda (C. odorata L.) leaf extract. The measurements are higher than those reported for pomegranates (26 mm), apples (20 mm), and lemons (20 mm) against Staphylococcus aureus [13].…”
Section: Antibacterial Activity Testcontrasting
confidence: 94%
“…The antibacterial activity of Majapahit fruit extract was determined using the disc test (6 mm) with various doses in vitro. The basic principle of this method is to allow the extract to diffuse into a solid bacterial culture [6][7][8]. The identification of cell damage caused by V. harveyi was visualized through TEM.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) and Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Senyawa metabolit sekunder daun kirinyuh seperti flavonoid, alkaloid, tannin dan fenolik berfungsi sebagai antibakteri sehingga banyak dimanfaatkan dalam menyembuhkan penyakit akibat bakteri. Selain itu, penelitian oleh Harlina et al, 2015 menunjukkan bahwa ekstrak metanol daun kirinyuh konsentrasi 1250 ppm paling efektif dalam menghambat Vibrio harveyi penyebab vibrosis pada udang.…”
Section: Pendahuluanunclassified
“…Dilaporkan bahwa tanaman ini digunakan sebagai antibakteri, antiplasmodic, antiprotozoal, antijamur, antihipertensi, antiinflamasi [3]. Daun kopasanda ini terbukti positif mengandung senyawa bioaktif yakni senyawa fenolik, flavonoid, alkaloid dan tannin [4]. Berdasarkan hasil uji aktivitas anti bakteri senyawa bioaktif daun kopasanda mampu menghambat perkembangan bakteri dengan zona hambat 19 mm tergolong kuat sehingga mempunyai potensi untuk dikembangkan sebagai agen antibakteri untuk penanggulangan Vibriosis pada budidaya udang windu P. monodon [5].…”
Section: Pendahuluanunclassified